Lithium exposure during pregnancy increases fetal growth. (February 2021) - Poels, Eline MP; Sterrenburg, Karin; Wierdsma, André I; Wesseloo, Richard; Beerthuizen, Annemerle; van Dijke, Laura; Lau, Condon; Hoogendijk, Witte JG; Marroun, Hanan El; van Kamp, Inge L; Bijma, Hilmar H; Bergink, Veerle
Background: Lithium is an effective treatment in pregnancy and postpartum for the prevention of relapse in bipolar disorder, but there is a lack of knowledge about the potential adverse impact on fetal development. Aims: To investigate the impact of lithium exposure on early fetal growth. Methods: In this retrospective observational cohort study, we included all singleton pregnancies of women using lithium and referred for advanced fetal ultrasound scanning between 1994 and 2018 to the University Medical Centers in Leiden and Rotterdam, the Netherlands ( n =119). The Generation R study, a population-based cohort, served as a non-exposed control population from the same geographic region ( n =8184). Fetal head circumference, abdominal circumference, femur length, and transcerebellar diameter were measured by ultrasound at 18–22 weeks of gestation. Results: Lithium use during pregnancy was associated with an average increase in head circumference of 1.77 mm (95% confidence interval: 0.53, 3.01), in abdominal circumference of 5.54 mm (95% confidence interval: 3.95, 7.12) and in femur length of 0.59 mm (95% confidence interval: 0.22, 0.96) at 18–22 weeks gestation. Furthermore, lithium use during pregnancy was associated with an average increase in birth weight of 142.43 grams (95% confidence interval: 58.01, 226.89), whereas it was associated with an average decrease of 1.41 weeks in gestational duration (95% confidence interval: −1.78, −1.05). Conclusions: Lithium use during pregnancy was associated with increased fetal growth parameters at 18–22 weeks gestational age and increased birth weight. Further research is needed to evaluate both short- and long-term implications, as well as the mechanisms driving this difference in growth.